Problematic prospects for US-Turkish ties in the Biden era: Human rights, sanctions likely among early tests - Alan Makovsky (Stiftung Wissenschaft und Politik (SWP), 2020)
Minimal discussion of foreign policy during the US presidential campaign has left President-elect Joe Biden pinned to very few specific foreign policy positions and given him great flexibility in carrying out his program. He would probably prefer to avoid confrontation with Turkey; in fact, he will likely explore areas of potential US‑Turkish cooperation, especially against Russia. However, Biden's core positions on human rights and rule of law, his long-time focus on Aegean and Eastern Mediterranean issues, and his seeming inclination to continue to fight ISIS in cooperation with the Syrian-Kurdish People's Protection Units (YPG) militia - deemed 'terrorists' by Ankara - probably augur deepening difficulties in US-Turkish ties. Down the line, a make-or-break decision on the future of US-Turkish ties will likely hinge on the Biden Administration's assessment of Turkish-Russian relations. Europe may have an important say on Biden's Turkish policy; a senior Biden adviser has said the new president will coordinate his approach to Turkey with the European Union.
Keywords: 320